Applying Citizen Science for Sustainable Development: Rainfall Monitoring in Western Nepal - Paul, Jonathan D.; Cieslik, Katarzyna; Sah, Neeraj; Shakya, Puja; Parajuli, Binod Prasad; Paudel, Saugat; Dewulf, Art; Buytaert, Wouter (Frontiers in Water, 2020)
We introduce a case-study agnostic framework for the application of citizen science in a sustainable development context. This framework is tested against an activity in two secondary schools in western Nepal. While the purpose of this activity is to generate locally relevant knowledge on the physical processes behind natural hazards, we concentrate here on its implementation, i.e. to obtain a better understanding of the dynamic of the activity and to learn how it should be implemented. We determined the social capital of secondary schools as a gateway to the local community: they provide a unique setting to bring different stakeholders together. We find that co-designing a teaching programme is an effective means of both complementing local curricula and ensuring continued buy-in of local stakeholders (i.e. teachers). Student engagement depends on the local relevance of teaching materials, with more holistic or global concepts such as climate change of lesser importance. Our activity focused on rainfall, including student-led data collection. These rainfall data provide a very good fit to co-located rain gauge data, with an average difference on weekly readings of 11.8%, reducing to 8.3% when averaged over all student readings. The autonomous development of student-organised science clubs suggested that our original framework underestimated students’ capacity to apply knowledge elsewhere creatively. These clubs may be used to obtain participant feedback to improve and tailor future activities. Quantitative assessment of long-term sustainability remains challenging, due in part to high levels of student turnover. We suggest that integrating scientists wherever possible within a school or local community has a direct and positive result on participant retention.